Dispute Resolution Between Patients And Perpetrators Who Provide Access To The Contents of Electronic Medical Records (RME) Unlawfully - Hawreyvian Rianda Seputra; Imam Ropii; Carolina K; Marsudi Dedi Putra (Journal of Law, Politic and Humanities, 2025)
This study aims to describe and analyze the form of violation of the law committed by the perpetrator who gives unauthorized access to the content of RME documents that cause disputes with patients and analyzes the dispute resolution mechanism due to the violation of the law that harms the patient. The research method used is normative juridical with legislative, conceptual, and case approaches, and is supported by secondary data in the form of primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that: 1) Forms of violation of the law committed by perpetrators who provide unauthorized access to the contents of RME documents include opening, sending, or disseminating patient medical record data without consent or a valid legal basis, which is contrary to Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, and Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records,  so as to cause both material and immaterial losses for patients; 2) Dispute resolution due to violations of the law by the perpetrator who gives unauthorized access to the contents of RME documents that are detrimental to the patient can be pursued through civil law on the basis of Article 1365 of the Civil Code, where the patient has the right to file a lawsuit for compensation for unlawful acts, as well as non-litigation settlements such as mediation within the hospital or through alternative dispute resolution institutions,  However, the effectiveness of protecting patients' rights depends heavily on the implementation of an adequate data security system, health facilities' compliance with regulations, and the legal awareness of actors in maintaining confidentiality and protection of patient data.